Pengaruh Penggunaan Financial Technology pada UMKM Batagor Kaconk di UNISMA melalui Analisis SWOT - Ulyah, Nadiratul; Sabilla, Rizki; Bastomi, Mohamad (CV. Era Digital Nusantara, 2024)
This study investigates the impact of financial technology (fintech) usage, particularly digital wallets, on Batagor Kaconk MSMEs in the Unisma environment. The main objective of this research is to evaluate the benefits, ease, and challenges of fintech adoption in enhancing interest in digital payment usage. The SWOT analysis method was employed to conduct a comprehensive evaluation of the strengths, weaknesses, opportunities, and threats faced by Batagor Kaconk MSMEs in adopting fintech. The findings indicate that the adoption of fintech by Batagor Kaconk MSMEs, such as OVO, GoPay, Dana, Doku, ShoppePay, and LinkAja, has significantly benefited by improving transaction efficiency, expanding market reach, and reducing the risk of cash theft. However, challenges such as difficulties in operating new technologies, additional costs during transactions, and concerns about data security remain primary hurdles that need to be addressed. This research is expected to contribute to the development of more effective strategies in enhancing digital payment adoption among MSMEs, particularly in the food sector like Batagor Kaconk. Thus, MSMEs can better harness the potential of technology to support their growth and competitiveness in an increasingly digital market.